Selection of groundnut variety for making a good quality peanut butter - Dhamsaniya, Navnitkumar K. (Springer-Verlag, 2011)
Flavor and compositional quality are the ultimate criterion of the desirability of any food product. The nutritive value of any peanut product is closely associated with the fatty acid composition of its oil content, which influences its quality. Peanut butter was prepared using seven groundnut varieties commonly grown in major groundnut producing states of India. The flavor and compositional quality were determined using the standard procedures. The color code to the butter preparation was assigned by visually comparing the color of the butter with those given in the handbook of standard colors. On the basis of a combined evaluation, it could be recommended that the groundnut variety Somnath is the best-suited variety for producing peanut butter amongst the selected varieties.